History and theory of Islamic architecture - Spahic, Omer (IIUM Press, International Islamic University Malaysia, 2019)
Islamic architecture is a misunderstood subject. Quite often, as elementary -- and even trivial -- themes as defining Islamic architecture, the relationship between Muslim and Islamic architecture, and the prospect of existence of un-Islamic architectural expressions, hijack the entire intellectual discourses on Islamic architecture. This is so despite the fact that Islamic architecture existed since the dawn of Islamic culture and civilization approximately fourteen centuries ago. Islamic architecture, more often than not, was the most recognizable feature of that cultural and civilizational consciousness, serving at once as its face and epitome. Some of the reasons behind such misunderstandings could be due to the absence of a comprehensive and appropriate theory of Islamic architecture.Most studies on Islamic architecture by Muslims and non-Muslims are carried out through the prism of Western worldviews and value systems. Having encountered numerous difficulties in explaining adequately the theory and philosophy of Islamic architecture, on account of resorting to that particular and other similar in essence approaches, most authors were content just to describe Islamic architectural facts providing at best some superficial, patchy and, at times, even inaccurate theoretical rationalizations and explanations in the process. Worse still, the others were content to ignore the matter altogether and focus solely on the technical and artistic aspects instead. Those scholars and researchers failed to transcend their flawed academic methods and penetrate the essence and soul of the orb of Islamic architecture. Had they done so, they would have discovered a glaring incompatibility between Islamic architecture and the conceptual frameworks from which they approached and studied it. This would have called for more objective, thorough and honest scientific inquiries into the authentic meaning and character of Islamic architecture. There would have emerged, as a result, a different research culture among Muslim and non-Muslim Islamic architecture enthusiasts which, in turn, would have resulted in bequeathing to posterity a different type of intellectual legacy. This book intends to fill in somewhat the glaring intellectual gap in the sphere of authentic Islamic architecture. It provides a theoretical or philosophical framework for studying and teaching Islamic architecture on the basis of some of the most authentic sources of Islamic scholarship. Against the backdrop of such a broad framework, various Islamic architecture themes and dimensions could be more accurately studied and understood. The book is also envisaged as an invitation to other researchers and scholars from across the spectrum of especially Islamic scholarship to embark on similar undertakings and do justice to the fascinating phenomenon of Islamic architecture, enriching in the process academic communities and their libraries. The book is divided into seven chapters. Each chapter represents an individual study on a vital subject relating to the theoretical and epistemological foundation of Islamic architecture. Those chapters are as follows: 1. The Qur’an and Sunnah as a conceptual foundation of Islamic architecture; 2. The form and function of the Prophet’s Mosque during the time of the Prophet (pbuh); 3. God as the only Creator: some implications for conceptualizing Islamic architecture; 4. A conceptual framework for sustainability in Islamic architecture; 5. Rationalizing the permissibility of mosque decoration; 6. Towards an Islamization of housing and housing education; 7. Al-Wasatiyyah and Islamic built environment. One of the reasons why Muslim designers and architects lack will, courage, self-belief and orientation when it comes to designing and erecting buildings that are truly inspired by and harmonious with the message of Islam, i.e., to create elements of genuine Islamic architecture, is the lack of the appropriate educational plans and policies, the right literature and incessant productive discourses on the different aspects of Islamic architecture whereby Islamic architecture will be viewed not only as pure art, science and technology, but also as an intellectual discipline that extends into higher and more sophisticated ontological realms. Muslim architects and designers are short of unwavering and active exposures to such an intellectual climate. It follows that remedying and enhancing Islamic architectural education, coupled with boosting its literature and quality research culture, will go a long way in providing an antidote to Muslim architects’ and designers’ trepidation, scepticism and lack of confidence insofar as making contributions to reviving Islamic architecture at both conceptual and practical planes is concerned. This book is a step to that direction. It hopes to improve the awareness of the Islamic architecture professionals, educators and ordinary people -- that is, the Islamic architecture providers and users -- as to the significance of articulating, teaching and putting into operation the bona fide theory and philosophy of Islamic architecture. The book’s contents are conceptual, or philosophical, rather than empirical.